2003
DOI: 10.1046/j.1365-2141.2003.04497.x
|View full text |Cite
|
Sign up to set email alerts
|

Disease activity and pretreatment, rather than hypogammaglobulinaemia, are major risk factors for infectious complications in patients with chronic lymphocytic leukaemia

Abstract: To identify patients at high risk of life-threatening infections, we retrospectively analysed the prevalence of infectious complications in 187 chronic lymphocytic leukaemia patients treated in our institution since 1999 and correlated them with clinical features. A questionnaire with detailed questions regarding infectious complications was mailed to patients and their general practitioners. Major infections (requiring intravenous antibiotics or inpatient treatment) were reported in 37 patients (19.8%) and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 16 publications
2
48
0
2
Order By: Relevance
“…Indeed, a great proportion of patients with unmutated IgV H genes require chemotherapy, which also may increase their risk of infections. 23,25 It is surprising that ZAP-70 expression was not predictive of infection risk, given the reported strong correlation between ZAP-70 expression and IgV H mutation status. 4 Our correlation was around 60%, clearly below most reported series, 4 implying that our ZAP-70 results must be regarded with caution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, a great proportion of patients with unmutated IgV H genes require chemotherapy, which also may increase their risk of infections. 23,25 It is surprising that ZAP-70 expression was not predictive of infection risk, given the reported strong correlation between ZAP-70 expression and IgV H mutation status. 4 Our correlation was around 60%, clearly below most reported series, 4 implying that our ZAP-70 results must be regarded with caution.…”
Section: Discussionmentioning
confidence: 99%
“…7,10,23,25 Several predisposing factors have been suggested over the last 50 years, including hypo-g-globulinemia, neutropenia, defective T-cell function, and reduced complement activity. 7,26 In keeping with previous reports, the infective pattern observed in the current work was very similar to that observed in primary humoral immune deficiencies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of factors have been identified that contribute to increased risk of infection in patients with CLL, including age, type and/or number of prior treatments, and immune cell status [21,27,36]. A retrospective analysis of 187 patients with CLL demonstrated that the number of chemotherapy (p<0.001), purine analogue (p<0.001), and monoclonal antibody treatments (p=0.019) significantly increased the risk for major infections [21].…”
Section: Patient Predisposition To Infectionsmentioning
confidence: 99%
“…A retrospective analysis of 187 patients with CLL demonstrated that the number of chemotherapy (p<0.001), purine analogue (p<0.001), and monoclonal antibody treatments (p=0.019) significantly increased the risk for major infections [21]. Due to the chronic nature of CLL and subsequent disease relapses, most patients receive more than one treatment over the course of the malignancy.…”
Section: Patient Predisposition To Infectionsmentioning
confidence: 99%